RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND ACTION WITH PERSONAL HYGIENE OF FOOD HANDLERS AT NUTRITION INSTALLATION RADEN MATTAHER HOSPITAL JAMBI - Magdalena Naibaho (Universitas Widya Gama Mahakam Samarinda, 2023)
RESEARCH BACKGROUND : Personal hygiene is an effort to maintain the cleanliness of employees and food handlers through routine checks on the cleanliness of hair, teeth and mouth, nails, work clothing and work appearance. The purpose of personal hygiene is to prevent food contamination of food handlers at the Nutrition Instalation. This study was to determine the Relationship Of Knowledge, Attitude And Action With Personal Hygiene Of Food Handlers At The Nutrition Installation Of Raden Mattaher Hospital Jambi METHODE : This research is a quantitative research with a cross sectional research design. The population is all officers who are responsible for the Nutrition Installation at the Raden Mattaher General Hospital Jambi, totaling 35 people, and the sample is determined using a total sampling technique. Retrieval of data using questionnaires, observations and interviews. Statistical test using the chi square test. RESULT : The results showed that knowledge was not good (20%), attitudes were not good (43.8%) and actions were not good (40.6%). The results of the bivariate analysis showed that there was an effect between knowledge and personal hygiene (P = 0.033), there was an effect between attitudes and personal hygiene (P = 0.181) and there was an effect between action and personal hygiene (P = 0.030). RECOMMENDATION : for Nutrition Installations to increase knowledge, attitudes and actions of food handlers by counseling, personal hygiene training, and increasing supervision performance or behavior of food handlers.